2017
DOI: 10.1039/c7tc01285c
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence properties and energy transfer of YGa1.5Al1.5(BO3)4:Tb3+,Eu3+ as a multi-colour emitting phosphor for WLEDs

Abstract: Energy-transfer-based multi-colour emissions in YGa1.5Al1.5(BO3)4:Tb3+,Eu3+ for WLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…It is significant that luminescent intensity of CZGO:0.16Eu at 423 K (150°C) still maintains as much as 91.01% of that measured at room temperature upon 370 nm light irradiation. These results suggest that the as‐prepared phosphors display highly thermal stability, which is superior to that of most reported single‐phased phosphors for UV‐LEDs . The activation energy ( E a ) for thermal quenching of emission of CZGO:0.16Eu can be calculated via Arrhenian Equations,Ifalse(Tfalse)=I01+Cexp(-EaitalickT)where I 0 and I(T) represent the luminescent intensities at room temperature and different temperatures, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is significant that luminescent intensity of CZGO:0.16Eu at 423 K (150°C) still maintains as much as 91.01% of that measured at room temperature upon 370 nm light irradiation. These results suggest that the as‐prepared phosphors display highly thermal stability, which is superior to that of most reported single‐phased phosphors for UV‐LEDs . The activation energy ( E a ) for thermal quenching of emission of CZGO:0.16Eu can be calculated via Arrhenian Equations,Ifalse(Tfalse)=I01+Cexp(-EaitalickT)where I 0 and I(T) represent the luminescent intensities at room temperature and different temperatures, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…These results suggest that the as-prepared phosphors display highly thermal stability, which is superior to that of most reported single-phased phosphors for UV-LEDs. [37][38][39][40][41] The activation energy (E a ) for thermal quenching of emission of CZGO:0.16Eu can be calculated via Arrhenian Equations 31,42 , where I 0 and I(T) represent the luminescent intensities at room temperature and different temperatures, respectively. C corresponds to a constant, while k stands for the Boltzmann constant (8.625 × 10 −5 eV/K).…”
Section: Resultsmentioning
confidence: 99%
“…Li et al . reported the multicolour emission of YGa 1.5 Al 1.5 (BO 3 ) 4 (YGAB):Tb 3+ ,Eu 3+ and found that the distribution of the isolated sites in the crystalline lattice affected the luminescence properties and energy transfer mechanism . The interaction between the luminescence centres is weak, owing to the large distance between the paired ions in the same unit cell and therefore concentration quenching is less.…”
Section: Development Of New Phosphorsmentioning
confidence: 99%
“…Moreover, the excitation of 7 F 0 / 5 D 3 , 5 L 6 (Eu 3+ ) overlaps with the emission of 5 D 3 / 7 F 5 (Tb 3+ ). 35 To further investigate the energy transfer process, a series of samples of GdSr 2 AlO 5 :2%Tb 3+ ,x%Eu 3+ (x ¼ 0, 0.5, 1, 2, 3, and 5) were prepared whose emission spectra under the excitation at 275 nm are presented in Fig. 5(a).…”
Section: Luminescence Propertiesmentioning
confidence: 99%